(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
It is proposed that Poly(Trimethylene Terephthalate) (PTT) filaments are used for fabricating vascular prostheses instead of Poly(Ethylene Terephthalate) (PET) because of their lower Young's modulus and superior elastic recovery. The heat setting process is necessary to keep the stability of shape and mechanical properties as well as making the flattened tubular structures round. However, the best heat setting condition for keeping properties of lower Young's modulus and superior elastic recovery of PTT filaments is unknown. This paper studies the influence of different heat setting conditions to the change of Young's modulus and elastic recovery. The temperature range is chosen from 120 to 180 °C and time period is chosen from 30 s to 90 s. The heat setting of yarns is both done in the relaxation state and tension state. Results show that the best heat setting conditions to get lower modulus, higher elastic recovery and better creep property at the temperature of 160 °C under the tension state through 60 s. The tension or relaxation state has the biggest influence on elastic recovery and Young's modulus while time period has the least influence.